The Awesome Adventures of Will and Randolph: Battle of the Blockheads - Archer, Jeffrey (Saga Egmont, 2024)
Dive into a world of magic, mystery, and square-shaped trees, and join brave boy Will, his talking teddy bear Randolph, and their quirky Upside-Down Bird friend! Transported by an ancient medallion to Whispering Woods - where blobs talk and trees are cube-like - our heroes find themselves caught in a sticky situation. How will they get home? Why is their bird friend upside-down? And can they stop the block-headed war between Big Whoosh\'s forest folk and Quagmire’s swampy Bloblins? Get ready for a tale filled with thrilling escapes, laugh-out-loud moments, clever disguises (some not so successful)...and above all else – the value of friendship! When Will receives a mystical amulet, it brings his toy bear Randolph to life! This triggers a cascade of adventures where every book catapults them into peculiar new worlds. With Toy Story-like charm and Mr Benn\'s magical touch, this series follows their journey as they tackle moral dilemmas with courage and humour. Jeffrey Archer (1940-) is a bestselling British author and former politician, renowned for his captivating novels, short stories, and children\'s books published in over 97 countries and over 37 languages. His best-known works include ‘First Among Equals’, ‘Kane and Abel’ and ‘Only Time Will Tell’.